Genetic Polymorphism of NAT2 Metabolizing Enzymes on Phenytoin Pharmacokinetics in Indian Epileptic Patients Developing Toxicity - Murali, M.; Manjari, T.; Madhuri, B.; Raghavan, S.; Jain, D.C.; Vivekanandhan, S. (CNS neuroscience & therapeutics, 2012)
SUMMARY  Objective: To investigate the effects of NAT2 metabolizing enzymes on the pharmacokinetics of antiepileptic drug phenytoin in the epileptic patients showing toxicity. Methods: Fifty epileptic individuals who had developed toxicity to phenytoin and 50 control epileptic subjects who had not developed toxicity to phenytoin were genotyped for NAT2 (NAT2*5A, NAT2*5C, NAT2*7, NAT2*6) polymorphisms by polymerase chain reaction–restriction fragment length polymorphisms (PCR–RFLP method). Phenytoin plasma levels were analyzed by reversed phase HPLC method and pharmacokinetic parameters such as area under the concentration curve (AUC), maximum concentration (Cmax), time to Cmax (tmax) and half‐life (t1/2) were estimated by noncompartmental analysis using PK Solutions® software. Results: The NAT2 polymorphism was seen to be in Hardy–Weinberg equilibrium and showed significant genotypic as well as allelic association with phenytoin toxicity for NAT2*5A (481C>T) and NAT2*5C (803A>G). Pharmacokinetic parameters for phenytoin in toxicity group of poor metabolizers showed a longer elimination half‐life of a drug (t1/2= 35.3 h) and less clearance rate (CL = 468 mL/h) compared to intermediate metabolizers (t1/2= 33.2 h, CL = 674 mL/h) and extensive metabolizer (t1/2= 20.7 h, CL = 977 mL/h) in NAT2*5A polymorphism. Conclusion: Our findings suggest that the NAT2*5A genetic polymorphisms plays a significant role in the steady‐state concentrations of phenytoin and thereby have impact on toxicity in epileptic patients.